2015
DOI: 10.1007/s10936-015-9363-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Sarcasm to Compliment: Context, Intonation, and the Perception of Statements with a Negative Literal Meaning

Abstract: The present study extended findings of contrast effects in an auditory sarcasm perception task manipulating context and tone of voice. In contrast to previous research that had used sarcastic and sincere statements with a positive literal meaning, the present experiment examined how statements with a negative literal meaning would affect the results. Eighty-four undergraduate students completed a task in which an ambiguous, positive, or negative computer-generated context spoken in a flat emotional tone was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…In terms of the acoustic characteristics of ironic prosody, we found that classified as ironic stimuli had a slower speech rate than literal and unrelated statements, in agreement with previous studies ( Rockwell, 2001 ; Cheang and Pell, 2009 ; Bryant, 2010 ; Li et al, 2013 ; Peters et al, 2016 ; Voyer and Vu, 2016 ; Deliens et al, 2018 ). Ironic stimuli had higher median intensity and higher fundamental frequency (F0) (median and range) than unrelated statements only; others have found that ironic stimuli have greater intensity ( Rockwell, 2001 ; Li et al, 2013 ; Peters et al, 2016 ; Deliens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of the acoustic characteristics of ironic prosody, we found that classified as ironic stimuli had a slower speech rate than literal and unrelated statements, in agreement with previous studies ( Rockwell, 2001 ; Cheang and Pell, 2009 ; Bryant, 2010 ; Li et al, 2013 ; Peters et al, 2016 ; Voyer and Vu, 2016 ; Deliens et al, 2018 ). Ironic stimuli had higher median intensity and higher fundamental frequency (F0) (median and range) than unrelated statements only; others have found that ironic stimuli have greater intensity ( Rockwell, 2001 ; Li et al, 2013 ; Peters et al, 2016 ; Deliens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the prosody of ironic statements had a lower fundamental frequency (F0) than literal statements, this difference was not statistically significant as expected based on the literature ( Rockwell, 2001 ; Li et al, 2013 ; Peters et al, 2016 ; Deliens et al, 2018 ). One possibility is that the specific acoustic conventions to express irony may differ between languages, as has been suggested ( Rockwell, 2001 ; Cheang and Pell, 2009 ; Bryant, 2010 ; Li et al, 2013 ; Peters et al, 2016 ; Voyer and Vu, 2016 ; Deliens et al, 2018 ). Another is that the acoustic correlates of ironic prosody are not intrinsic but relative to the enfolding discourse ( Bryant, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small dataset of only 2000 tweets was used; hence, Naïve Bayes worked well. Voyer and Vu [24] developed a model to experiment how negative literal statements would affect sarcasm detection in auditory perception. e approach achieved 80% accuracy in sarcasm identification.…”
Section: Literature Survey On Sarcasm Detectionmentioning
confidence: 99%
“…e polarity and sentiment score for these tweets are analyzed using TextBlob and NLTK. e change in mood 0 10 20 30 40 50 60 70 80 90 100 Accuracy (%) State-of-the-art approaches Mukherjee et al [25] Mazen et al [24] Jihen et al [21] Jayasanka et al [56] Rajadesingan et al [34] Proposed work Figure 9: Comparison of the proposed system with existing approaches. Figure 10: Sarcastic type classification based on proposed multi-rule approach.…”
Section: Modelling User's Mood Changementioning
confidence: 99%